2016
DOI: 10.1111/ppc.12171
|View full text |Cite
|
Sign up to set email alerts
|

Acknowledging Rural Disadvantage in Mental Health: Views of Peer Workers

Abstract: The identified barriers place limitations on the capacity of peer workers to maximize effectiveness in rural settings. Peer workers could potentially play an important role in overcoming shortages of staff and services and improving mental health service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…We can only say that there is no record of such actions. However, these findings are congruent with the literature, which indicates rural community members often lack understanding of mental health and suicide (Broffman et al, 2017), may have dismissive or stigmatizing attitudes toward mental health problems (Hayslip et al, 2010; Judd et al, 2006), and may have difficulty accessing mental health services (Broffman et al, 2017; Byrne et al, 2017; Fraser et al, 2005). More research is needed to understand the behaviors of families in response to farmers’ suicidal threats.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We can only say that there is no record of such actions. However, these findings are congruent with the literature, which indicates rural community members often lack understanding of mental health and suicide (Broffman et al, 2017), may have dismissive or stigmatizing attitudes toward mental health problems (Hayslip et al, 2010; Judd et al, 2006), and may have difficulty accessing mental health services (Broffman et al, 2017; Byrne et al, 2017; Fraser et al, 2005). More research is needed to understand the behaviors of families in response to farmers’ suicidal threats.…”
Section: Discussionsupporting
confidence: 81%
“…Some research has suggested a link between depression and exposure to pesticides as well (Onwuameze, Paradiso, Peek-Asa, Donham, & Rautiainen, 2013). Finally, rural communities often lack adequate health and behavioral health services, making help-seeking challenging for those farmers who may wish to obtain services (Broffman et al, 2017; Byrne, Happell, & Reid-Searl, 2017; Fraser et al, 2005).…”
mentioning
confidence: 99%
“…Furthermore, Dallas police officers mainly live outside the city, where access to mental health services is typically more difficult than within urban areas. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Rather than limit consumer leadership to conventional leadership roles, advocates call for its recognition in diverse roles both throughout and outside of the mental health system (Byrne et al . ; Piat et al . ).…”
Section: Introductionmentioning
confidence: 99%